PERANCANGAN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA MENGGUNAKAN SOLAR TRACKER DUAL AXIS DAN MONITORING DATA LOGGER BERBASIS INTERNET OF THINGS (IOT) - Nanda, Nanda Bagus Setiawan; Priyandoko , Gigih; Mukhsim, Mohammad (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2024)
The tool is designed to ensure that solar panels are always positioned perpendicular to the sun using an Arduino Uno as an automatic controller, along with other components such as light sensors (LDR) and DC motors. This microcontroller operates by processing data from the LDR sensors using programming on the Arduino Uno. When the LDR sensor is not aligned with the sun, its resistance value will differ. If this difference occurs, the microcontroller will move the motor to adjust the solar panel until the resistance returns to an equal value. The data logger monitoring aims to track the power capacity of the solar panels. Arduino is capable of generating optimal voltage when the solar panel is perpendicular to the direction of the sun. Based on tests conducted by comparing static solar panels with solar panels equipped with dual-axis trackers, it was found that solar panels with dual-axis trackers have a more optimal solar energy absorption capability. This is evident from the measurement of the electrical voltage generated, where the voltage on solar panels with dual-axis trackers is higher compared to static solar panels or those using single-axis trackers. The data obtained shows an increase in voltage starting at 09:00, with the maximum voltage recorded at 13:00, before eventually declining. The Data Logger can be monitored using the Blynk application, allowing it to be tracked through the Internet of Things (IoT).